Characteristics of creative students based on academic performance in Faculty Management (FM) - Khairunnajah Mustaffa Albakri, author 612212 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2018